Development of a New Model for Cascade Fuzzy Logic Controller Based on DC-DC Boost Converter to Track the Maximum Power Point of Photovoltaic Energy Systems - Imane Dilaneh (Tishreen University, 2020)
The research presents a new model of a Cascade Fuzzy Logic Controller (CFLC) to track the Maximum Power Point Tracker (MPPT) for photovoltaic solar PV systems. The MPPT-CFLC controller proposed to track the MPP, is achieved in two consecutive stages. In the first stage, the optimum operating voltage (VMPP) is evaluated using the VMPP Fuzzy Logic Estimator (VMPP-FLE). In the second stage, the duty cycle (D), which is used to control the DC-DC Boost Converter switching cycle, is determined using a DMPP-FLC controller. The error resulting from the comparison of the output voltage of  VMPP-FLE and of the PV system, and the resulting error change are the input variables of the DMPP-FLC, which is used to determine the DMPP. Thus, the efficiency of the performance of the proposed Cascade controller model depends on the efficiency of the VMPP-FLE model in assessing the value of VMPP at different atmospheric variations and on the efficiency of the DMPP-FLC Controller in determining the optimum operating rate. Thus, this special structure of the MPPT-CFLC controller resulting from the cascade connection of the two models VMPP-FLE and DMPP-FLC will improve the dynamic performance of the proposed controller and achieve accuracy in MPP tracking. Thus, the MPPT-CFLC model proposed in the research is a new and different model of the reference FLC models, which is based on the simulation of the work of Conventional-tracking techniques such as Perturb and Observer technique, Incremental conductance technique. The simulation results performed in the Matlab/Simulink environment demonstrated the best performance of the proposed controller by improving the dynamic and static response of the PV system compared with the use of several other Fuzzy Logic and Neuronal reference models. يقدم البحث نموذج جديد لمتحكم عائم تسلسلي (Cascade Fuzzy logic Controller, CFLC ) لتتبع نقطة الاستطاعة العظمى  (Maximum Power Point Tracker, MPPT) لنظم الطاقة  الكهروضوئية PV. يتحقق عمل المتحكم العائم التسلسلي MPPT-CFLC المقترح وفق مرحلتين متتابعتين. يتم في المرحلة الأولى، تقدير توتر التشغيل الأمثل (Voltage of Maximum Power Point, VMPP) لنظامPV   باستخدام نموذج مقدر توتر نقطة MPP العائم المطور في البحث (VMPP Fuzzy logic Estimator, VMPP-FLE). أما في المرحلة الثانية، يتم تحديد قيمة نسبة التشغيل المناسبة المثلى (Duty cycle, D) الموافقة للتوترVMPP، والمستخدمة للتحكم في دورة عمل مبدل رافع الجهد المستمر، باستخدام نموذج لمتحكم عائم DMPP-FLC)  DMPP Fuzzy logic Controller,). حيث يشكل الخطأ الناتج من مقارنة توتر التشغيل VMPP-FLE مع توتر خرج نظام PV، وتغير الخطأ الناتج متغيرات الدخل للمتحكم العائم DMPP-FLC، المستخدم لتحديد نسبة التشغيل DMPP. بالتالي، يعتمد كفاءة أداء عمل نموذج المتحكم العائم التسلسلي المقترح على كفاءة عمل نموذج مقدر التوتر العائم VMPP-FLE في تقدير قيمة VMPP عند التغيرات الجوية المختلفة، وعلى كفاءة المتحكم العائم  DMPP-FLCفي تحديد قيمة  نسبة التشغيل الأمثل. بالتالي، هذا التركيب الخاص للمتحكم MPPT-CFLC الناتج من الربط على التسلسل للنموذجين VMPP-FLE DMPP-FLC, من شأنه تحسين الأداء الديناميكي للمتحكم العائم المقترح، ويحقق دقة في تتبع نقطة MPP.  بالتالي، يعتبر نموذج المتحكم العائم التسلسلي MPPT-CFLC المقترح في البحث، نموذج جديد ومختلف عن نماذج المتحكمات العائمة المرجعية والتي تعتمد في عملها على محاكاة عمل تقنيات التتبع التقليدية كتقنية الاضطراب والمراقبة وتقنية زيادة الناقلية. أظهرت نتائج المحاكاة المنجزة في بيئة Matlab/Simulink الأداء الأفضل للمتحكم المقترح، بتحسين الاستجابة الديناميكية والاستاتيكية لنظام PV مقارنة مع استخدام عدة نماذج مرجعية أخرى عائمة وعصبونية.